Population status and sustainability of Yellow-crested cockatoo (Cacatua sulphurea sulphurea) on Pasoso Island, Central Sulawesi, Indonesia - Moh. Ihsan; ANI MARDIASTUTI; BURHANUDDIN MASY’UD; YENI A. MULYANI (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Ihsan M, Mardiastuti A, Masy’ud B, Mulyani YA. 2021. Population status and sustainability of Yellow-crested cockatoo (Cacatua sulphurea sulphurea) on Pasoso Island, Central Sulawesi, Indonesia. Biodiversitas 22: 3277-3283. Yellow-crested cockatoo (Cacatua sulphurea sulphurea) is a sub-species of Cacatua sulphurea which is spread in Sulawesi and several surrounding islands, including on Pasoso Island. This cockatoo population is under tremendous pressure until categorized as critical. So far, there is no comprehensive information about population status and sustainable population size. The objective of this research area was to assess the current status or size of the population, study the size of the sustainable population and study the determinants factor of the Yellow-crested cockatoo population sustainability on Pasoso Island. The result showed that the population of the Yellow-crested cockatoo in Pasoso Island was only 3 individuals, consists of 2 adults as the parent, and 1 young individual. From 5 analyzed scenarios of the minimum sustainable population size, the 4.1 scenario is the best scenario to maintain the sustainability of the Yellow-crested cockatoo population on Pasoso Island, which is a minimum population size of four pairs (8 adult individuals). The determinants of population sustainbility analysis with the minimum sustainable population size (8 individuals or 4 pairs of broodstock) showed that inbreeding and predation as determinant factors. These factors need to be controlled through mating management and predator control by both humans and carnivorous animals.